Mobilizing Social Resources to Promote the Societalization of Education in Vietnam - Trang, Nguyen Thi Huyen; Hoai, Tran Thi (VNU Journal of Science: Education Research; Vol 34 No 1, 2018)
Based on the Vietnamese Government’s documents and the practice of societalization of education (SE) in Vietnam over the past years, the paper presents the main causes of the ineffectiveness of SE's policy and compares Vietnam’s SE with the basic characteristics of a general social movement. The paper concludes that there was a need of mobilizing social resources to promote the SE in the current context.